Preclinical assessment of dual CYP26[A1/B1] inhibitor, DX308, as an improved treatment for keratinization disorders - J.G.S. Veit; Y. Poumay; D. Mendes; J. Kreitinger; L. Walker; A. Paquet; C. Menigot; F. Zolezzi; A.S. Paller; P. Diaz (Skin Health and Disease, 2021)
Abstract Background Retinoid‐based therapies are commonly used in the treatment of disorders of keratinization and other skin disorders but can result in non‐specific effects and adverse reactions. Use of retinoic acid metabolism blocking agents (RAMBAs) such as DX308 may address these shortcomings. Objectives Characterize the therapeutic potential of recently discovered, CYP26‐selective RAMBA, DX308. Materials and Methods Preliminary in vitro assessment of potential off‐target activity, metabolic and toxicologic profiling. Studies to assess safety and efficacy of topical treatment in correcting abnormal skin morphology in rhino mice. Extensive gene expression profiling by RNA sequencing and qPCR in 3D epidermis grown with keratinocytes (KCs) from keratinization disorders and healthy controls, to investigate modulation of retinoid biopathways. Results In vitro, DX308 does not interact with off‐target nuclear receptors or CYP450s, is not genotoxic, and is stable in skin, despite vigorous hepatic metabolism. In vivo, topical DX308 induces comedolysis and epidermal thickening without apparent adverse effects. Gene expression profiling shows potent modulation of retinoid‐responsive genes by DX308 in both healthy and keratinization disorder KCs. Pathway analysis suggests DX308 may inhibit inflammatory and immune responses in KCs. Conclusions These preliminary studies suggest that DX308 is an efficacious topical therapeutic with a favourable metabolic and safety profiles. DX308 may present an improved therapeutic alternative for the treatment of keratinization disorders and other retinoid‐responsive skin ailments.